2005
DOI: 10.1016/j.ydbio.2005.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Function and regulation of Alx4 in limb development: Complex genetic interactions with Gli3 and Shh

Abstract: The role of the aristaless-related homeobox gene Alx4 in antero-posterior (AP-) patterning of the developing vertebrate limb has remained somewhat elusive. Polydactyly of Alx4 mutant mice is known to be accompanied by ectopic anterior expression of genes like Shh, Fgf4 and 5'Hoxd. We reported previously that polydactyly in Alx4 mutant mice requires SHH signaling, but we now show that in early Alx4-/- limb buds the anterior ectopic expression of Fgf4 and Hoxd13, and therefore disruption of AP-patterning, occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 55 publications
6
56
0
1
Order By: Relevance
“…This suggests that in certain cellular contexts, Gli3 binding to a regulatory region may indirectly promote anterior expression, perhaps by blocking the action of some other repressive function. However, analysis of one of these genes, Alx4, has identified a regulatory region that recapitulate Gli3-dependent expression and this region shows no GBRs in our data set (Kuijper et al 2005).…”
Section: ;Gli3mentioning
confidence: 64%
“…This suggests that in certain cellular contexts, Gli3 binding to a regulatory region may indirectly promote anterior expression, perhaps by blocking the action of some other repressive function. However, analysis of one of these genes, Alx4, has identified a regulatory region that recapitulate Gli3-dependent expression and this region shows no GBRs in our data set (Kuijper et al 2005).…”
Section: ;Gli3mentioning
confidence: 64%
“…Mutations in WNT5A are causing the dominant Human Robinow syndrome, characterized by short stature, limb shortening, genital hypoplasia and craniofacial abnormalities [35]. ALX4 loss of function mutations cause polydactily in the mouse, through disregulation of the sonic hedgehog (SHH) signaling factor [36], [37]. Moreover, the ALX4 protein has been shown to bind proteins from the HOXA (HOXA11 and HOXA3) and HOXC (HOXC4 and HOXC5) clusters [38].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of polydactyly mutations showed that Shh transcription is negatively regulated by several genes including Fgf, Gli3, and aristaless-like 4 (Alx4). Deficiency in Gli3, which encodes a zinc finger protein that acts as a transcription factor, leads to the extra toes (Xt) mutation, and the Alx4 is considered to be linked to the mouse mutant Strong's luxoid (Lst) Qu et al, 1998;Kuijper et al, 2005;Panman et al, 2005). During limb bud development, Alx4 becomes critical for repression of anterior ectopic Shh expression (Qu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%